ANALYSIS OF PRICE PERCEPTION, PURCHASE INTEREST AND MARKETING PERFORMANCE ON PURCHASE DECISIONS - Niu Haitao (Dinasti Publisher, 2022)
Literature Review Review of Price Perception Analysis, Purchase Interest and Marketing Performance on Purchase Decisions is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Price Perception is related to Purchase Decisions; 2) Buying Interest is related to Purchase Decision; and 3) Marketing Performance related to Purchase Decision. Apart from these 3 exogenous variables that affect the endogenous variables of Purchasing Decisions, there are still many other factors including Product Quality, Service Quality and Brand Image variables.